PERAN MANAJEMEN SUMBER DAYA MANUSIA KEPOLISIAN REPUBLIK INDONESIA DALAM PENEGAKAN HUKUM TERHADAP ANGKUTAN TRUK SAWIT YANG MELEBIHI KAPASITAS MUAT - Nurhapani, Nurhapani (Ensiklopedia Sosial Review, 2019)
the role of human resource management of the National Police already understands that public goods transportation is generally freight transport which is harmless and does not require special facilities, while special freight transportation is transportation that uses goods specifically designed in accordance with the nature and shape of goods transported both dangerous and non-hazardous goods that require special facilities. Article 161 of the LLAJ Law states that the transportation of public goods must meet the following requirements: a) the road infrastructure that is passed meets the provisions of the Road class; b) available logistics distribution centers and / or places to load and c) unload goods; and use goods cars. Motor vehicles carrying special goods must: a) fulfill safety requirements in accordance with the nature and shape of the goods being transported; b) given certain marks in accordance with the goods transported; c) park the vehicle in the designated place; d) dismantle and load goods in the designated place and by using tools in accordance with the nature and shape of goods transported operating at a time that does not interfere with security, safety, smoothness and order traffic and road transportation; and f) get recommendations from relevant agencies.